Ultrafast-nonlinear ultraviolet pulse modulation in an AlInGaN polariton waveguide operating up to room temperature - D. M. Di Paola (Nature Portfolio, 2021)
Nonlinearity enhancement in different materials is relevant for many scientific applications. Here the authors demonstrate pulse modulation in the UV regime due to polariton-based nonlinearity in an AlInGaN waveguide structure, including at room temperature.